Manager's Decision-Making Styles: A Case Study On Family Enterprises - Karademir, Ömer; Tutar, Hasan (Kahramanmaras Sutcu Imam Universitesi Sosyal Bilimler Dergisi, 2024)
The personality traits of the managers, their perception styles, management approaches and the way they evaluate the events can affect their decision-making styles. However, it is known that managers generally prefer one of the intuitive or rational decision forms in the management process. This study aimed to examine managers' decision-making behaviors within the rationality and heuristics framework. The research is designed as a case study, one of the qualitative research designs, as it aims to examine the decision-making styles of the managers in family businesses and which rational or intuitive decision-making style they prefer. The research sample was determined according to the purposive sampling technique and includes 19 family business managers. Research data were collected from 19 family business managers operating in different fields with the help of a semi-structured interview form. The collected data were analyzed according to qualitative content analysis. According to the research findings, managers use all rational, limited rational or intuitive decision-making types in their decision processes. Participants stated that the conjuncture and their way of evaluating events determine the decision-making process. The research results show that perceiving and evaluating the conditions in the decision-making process affects the decision-making process. This result shows that decisions are made depending on the perception of events and personality traits. This situation is critical because it shows that decisions are made according to factual/rational processes and subjective and perceptual processes